2000
DOI: 10.1111/1467-8535.00159
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a series of cal modules on cell biology for undergraduate nursing students

Abstract: Introduction and rationaleThis project was undertaken at the University of Nottingham and was funded by the university's Teaching Enhancement Office using TLTP funding. Aside from the reported benefits of CAL as a method of delivery such as the development of lifelong skills and the scope for student directed learning, there were also more specific reasons for developing these packages. Students previously studied Cell Biology by looking at photographic slides of histology preparations and evaluations had indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In an empirical study, university students who found slides an unsatisfactory teaching medium rated a number of CAL packages positively, referring to them as 'interesting', 'getting your attention', 'giving instant feedback' and 'permitting you to work at your own pace'. The authors did not report on learning outcomes, but they highlighted the need for a range of teaching approaches (Wharrad et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In an empirical study, university students who found slides an unsatisfactory teaching medium rated a number of CAL packages positively, referring to them as 'interesting', 'getting your attention', 'giving instant feedback' and 'permitting you to work at your own pace'. The authors did not report on learning outcomes, but they highlighted the need for a range of teaching approaches (Wharrad et al, 2000).…”
Section: Introductionmentioning
confidence: 99%